2019
DOI: 10.1111/1471-0528.15926
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic quantification of total serum bile acids as a monitoring strategy for women with intrahepatic cholestasis of pregnancy receiving ursodeoxycholic acid treatment: a cohort study

Abstract: Objective To evaluate enzymatic total serum bile acid quantification as a monitoring strategy for women with intrahepatic cholestasis of pregnancy (ICP) treated with ursodeoxycholic acid (UDCA). Design Cohort.Setting One UK university hospital.Population 29 ICP cases treated with UDCA.Methods Serial samples were collected prospectively throughout gestation. Total serum bile acids were measured enzymatically and individual bile acids by high-performance liquid chromatographytandem mass spectrometry. Data were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
3
32
0
1
Order By: Relevance
“…Lower C4 concentrations were consistent with increased negative feedback on de novo hepatic bile acid synthesis through fibroblast growth factor receptor 4/ beta-klotho hepatic signalling. This finding is consistent with reports of reduced serum concentrations of the endogenous primary bile acids in UDCA-treated women 15 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Lower C4 concentrations were consistent with increased negative feedback on de novo hepatic bile acid synthesis through fibroblast growth factor receptor 4/ beta-klotho hepatic signalling. This finding is consistent with reports of reduced serum concentrations of the endogenous primary bile acids in UDCA-treated women 15 .…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that an increase in the CDCA:CA ratio occurs in the serum of women with ICP during UDCA treatment 15,21 . We conclude that hepatic bile acid synthesis via the classical pathway to produce CA is more affected by UDCA treatment than intra-and extra-hepatic synthesis of CDCA via the alternative pathway, secondary to the hepatic action of FGF19.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Analysis of the biochemical indicators determined in the blood serum of pregnant women with ICP indicates an increased concentration of bile acids as well as hepatic transaminases (Glantz, Marschall, & Mattsson, 2004). An increased, uncontrollable secretion of bile acids has a negative effect on the fetus (Manna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%